ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS HIDUP PASIEN KANKER KEPALA DAN LEHER DI RSUP SANGLAH - Nirmala, Made Sinta Ayu Suci; Tusta Adiputra, Putu Anda; Setiawan, I Gede Budhi; Yuniawaty Wetan, Ni Gusti Ayu Agung Manik (E-Jurnal Medika Udayana, 2022)
Head and neck cancer ranked as the fifth most common cancer in the world. A series of treatment is likely to cause changes in the quality of life in cancer patients. This study aims to determine the factors that affect the patient's quality of life and the relationship between EORTC QLQ-H&N35 and Karnofsky Performance Scale (KPS). This study is analytic with a cross sectional approach. The technique is total sampling adjusted to the inclusion and exclusion criteria. Data obtained were gender, age, anatomical location of head and neck cancer, stage of cancer, therapy, KPS, and EORTC QLQ-H&N35. Data was collected for 3 months and 45 samples were obtained. There were 24 patients ((53.3%) above 45 years old. 33 men (73.3%) and 12 women (26.7%). The most cases were nasopharyngeal cancer is 25 people (55.6%). A total of 19 patients (42.2%) were in stage IV. The most used therapies were surgery, chemotherapy, and radiotherapy is 19 people (41.3%). The mean KPS is 72.23 ± 16.992. The factor affect the quality of life of head and neck cancer patients the most is weight loss with a mean of 59.49 ± 49.989 and a significant correlation (p=0.000, p<0.05) between EORTC QLQ-H&N35 and KPS.